PELATIHAN PENGEMBANGAN INSTRUMENT TEST DIAGNOSTIK THREE-TIER DI MGMP KIMIA JAKARTA SELATAN 2 - Syaadah, Rika Siti; Nanda, Elsa Vera; Dianhar, Hanhan (LPPM Universitas Bina Bangsa, 2024)
Chemistry considered as diffiuclt subject because studies abstract things. Atomic structure is one of chemistry fundamental topic which is abstract. Most of students have misconception about this topic. Misconceptions held by student will caused students to have difficulty in learning other chemical materials. This community service activity aims to improve the competence of chemistry teachers in MGMP South Jakarta 2 in developing three-tier diagnostic test insturments to detect misconceptions. The methods used are presentations, group discussions, and three-tier misconception identification practice. The results show that the teacher are enthusiastic in participating to join this community service activity and have a high motivation to develop diagnostic test instrument on other chemical materials. This activity is expected to help the teachers in diagnosing student learning difficulties, so the teachers can choose more veried learning strategies to implement in learning activities then students’ understanding of chemical materials can be improved